The Potentials of Ecological Thinking for Music Education Professionalism : A Scoping Review - Treacy, Danielle; Thomson, Katja; Odendaal, Albi (Springer, 2026)
This chapter explores ecological thinking in music education research through a scoping review. Based on our analysis of 24 documents identified through a systematic search strategy, we identified seven thematic groups of theoretical or phenomenal congruence: bioecological model of human development; learning ecologies; teacher agency; ecological literacy; musical experience; quality of learning environments; and perception. The diversity of these thematic groups represents various ventures into ecological thinking in music education, and we argue that these lines of thinking hold potential for responding to recent calls for a changing professionalism in music education. Ecological thinking devotes attention to issues of interconnectedness and complexity, thereby preparing the ground for a transition in music education discourse from an ego-logical towards an eco-logical rationality. It supports reaching beyond music-only thinking to consider the ethical responsibility of the musical professional in relation to the world. Paradoxically, however, some ecological theorisation still centres the individual, and we conclude by proposing that researchers and practitioners explore theoretical ideas such as adaptive change theory within music education to further support transitions from ego-logical to eco-logical rationalities.
Keywords: musiikkikasvatus; opetus; ammatillinen kehitys; ekologia; musiikkifilosofia; ekomusikologia